A new natural hybrid of Broughtonia (Orchidaceae) from Cuba - Mújica, Ernesto (Universidad de Costa Rica, 2015)
At Cabo San Antonio (Guanahacabibes Peninsula), Cuba in 2004, a single specimen of Broughtonia ortgiesiana (Rchb.f.) Dressler, and a related species, Broughtonia cubensis (Lindl.) Cogn., were both observed in flower simultaneously. In 2006, fruits were observed on B. ortgiesiana, and nine years later (2015) we noted five young plants in anthesis that displayed floral characteristics common to both species. Given the time frame and the blend of floral traits, we conclude that these five plants are the result of a natural hybridization event between the two Broughtonia species the details of which are described here.